1998
DOI: 10.1021/cm980438m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of the Negative Thermal Expansion Material Cubic ZrMo2O8

Abstract: A new phase, cubic ZrMo2O8, has been prepared by the low-temperature dehydration of ZrMo2O7(OH)2·2H2O. This material displays isotropic negative linear thermal expansion (α = −5.0 × 10-6 K-1) over a large temperature range. Unlike the previously reported cubic ZrW2O8, it does not undergo any phase transformations on heating at atmospheric pressure, and it does not display any pressure-induced phase transformations below 0.6 GPa at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
183
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(194 citation statements)
references
References 20 publications
9
183
2
Order By: Relevance
“…For example, for many years, cubic ZrMo 2 O 8 could only be prepared via a precursor route, whilst solid state synthesis gave monoclinic ZrMo 2 O 8 below 400 o C and trigonal ZrMo 2 O 8 above this temperature [16]. However, recent work by Readman et al has shown that cubic ZrMo 2 O 8 can be synthesised from the oxides in seconds at high temperatures (1090-1130 o C) [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, for many years, cubic ZrMo 2 O 8 could only be prepared via a precursor route, whilst solid state synthesis gave monoclinic ZrMo 2 O 8 below 400 o C and trigonal ZrMo 2 O 8 above this temperature [16]. However, recent work by Readman et al has shown that cubic ZrMo 2 O 8 can be synthesised from the oxides in seconds at high temperatures (1090-1130 o C) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides oxide-based materials [1][2], anomalous thermal expansion behavior has been observed in molecular framework materials containing linear diatomic bridges such as the cyanide anions [3][4][5][6]. Recent X-ray diffraction measurements have shown [6] that the hexagonal materials, Ag 3 Co(CN) 6 and Ag 3 Fe(CN) 6 , exhibit exceptionally large ("colossal") positive thermal expansion (PTE) along the a direction (α a = +140 × 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…These thermal expansion coefficients are an order of magnitude larger than those observed in any other material. Even simple cyanides such as Zn(CN) 2 are reported [5] to have an isotropic NTE coefficient (α V = -51 × 10…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations